2007
DOI: 10.1021/pr070446f
|View full text |Cite
|
Sign up to set email alerts
|

Glycomics of Proteoglycan Biosynthesis in Murine Embryonic Stem Cell Differentiation

Abstract: Glycosaminoglycans (GAGs) play a critical role in binding and activation of growth factors involved in cell signaling critical for developmental biology. The biosynthetic pathways for GAGs have been elucidated over the past decade and now analytical methodology makes it possible to determine GAG composition in as few as 10 million cells. A glycomics approach was used to examine GAG content, composition, and the level of transcripts encoding for GAG biosynthetic enzymes as murine embryonic stem cells (mESCs) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 122 publications
(157 citation statements)
references
References 88 publications
4
152
1
Order By: Relevance
“…Primers used in the qRT-PCR analysis are listed in supplemental Table S1. Real time reactions were performed using the iQ TM SYBR Green Supermix (Bio-Rad) as reported previously (29). All PCRs were performed in triplicate samples and repeated at least two times.…”
Section: Methodsmentioning
confidence: 99%
“…Primers used in the qRT-PCR analysis are listed in supplemental Table S1. Real time reactions were performed using the iQ TM SYBR Green Supermix (Bio-Rad) as reported previously (29). All PCRs were performed in triplicate samples and repeated at least two times.…”
Section: Methodsmentioning
confidence: 99%
“…It has recently been demonstrated that the cell surface glycan heparan sulfate (HS) contributes to self-renewal and differentiation of mESCs by regulating BMP, Wnt, and FGF signaling [21,[27][28][29]. The expression patterns of several other cell surface glycans have now been described in undifferentiated and differentiated mESCs and hESCs [30][31][32][33][34]. However, although these glycans may be involved in the regulation of the signaling required for ESC self-renewal, with the exception of HS, their functional roles have not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…We report here, for the first time, that the genetically targeted deletion of GnT-Va causes the altered gene expression of several glycosyltransferases and galectins in MEFs using a newly developed qRT-PCR transcript analysis platform [11]. We speculate that some of the inhibited invasiveness-related phenotypes in MEFs caused by deletion of GnT-Va may result, at least in part, from the combination of altered expression of these glycosyltansferases and/or galectins.…”
Section: Introductionmentioning
confidence: 85%